Exploring small stories of older adults elicited by virtual nature videos with a randomized online survey - Kars Otten; Thomas JL van Rompay; Jan-Willem JR van ‘t Klooster; Debby L Gerritsen; Gerben J Westerhof (Digital Health, 2024)
Objective Counteracting feelings of loneliness among older adults underscores the need to improve social well-being, for example, by sharing small stories. Interestingly, virtual representation of nature (VN) can stimulate social aspirations and trigger associations, which could be used as conversational material. Especially nature's characteristics of mystery and spaciousness seem promising. Therefore, it was investigated whether VN can elicit small stories in older adults using a randomized 2 (mystery: low vs. high) × 2 (spaciousness: low vs. high) design. Methods In total 118 participants (60 years and older) were recruited. Small stories, nature-relatedness, available nature opportunities and demographics were measured. The small stories were analysed with respect to story elements (sum range: 0–4) and storytelling characteristics (ease of storytelling, valence, social intention). Results The VN were able to elicited small stories: 97% ( N  = 115) contained at least one story element. Moreover, when participants felt more related to nature and assigned more positive valence to their story, they also had stronger intentions to use their story for social interaction. The VN characteristics of mystery and spaciousness showed no effects. Conclusion Not so much the characteristics of nature (mystery and spaciousness) as the characteristics of the participants (nature-relatedness) played an important role in eliciting and sharing small stories.